1. x + 4 = 28
x + 4 – 28
x = 24
2. y – 6.5 = 31
y – 6.5 – 31
y = 37.5
3. 8z = 40 + 3z
8z - 3z - 40
5z - 40
z = 40/5
z = 8
4. 10x = - 5x + 60
10x + 50x – 60
60x – 60
x = 60/60
x = 1
5. – 15y + 3 = - 36 – 18y
- 15y + 18y + 3 + 36
3y + 39
y = -39/3
y = -13
6. 2x + 4 + ( 3x – 4 ) =
3x + 12
2x + 4 + 3x -4 = 3x +
12
2x + 4 + 3x -4 - 3x - 12
2x - 12
x = 12/2
x = 6
7. 4 ( 3x + 2 ) – 8 = 5 (
2x + 3 ) + 5
12x + 8 – 8 = 10x + 15 + 5
12x – 10x = 20<+o:p>
2x = 20
x = 20/2
x = 10
8. 15x – 40 -5x -20 = 0
10x = 60
x = 60/10
x = 6
*9. 16x – ( - 2x – 4 ) –
( 5x – 3x + 2 ) = - 4x – ( -8x + 2 )
16x + 2x + 4 – 2x – 2 = -4x + 8x – 2
16x
- 2 = -2 -2
12x = -4
x = -4/12
x = -1/3
10. – ( 7x – 2 + 12 ) + (
-5x – 3x + 4 ) = - ( -x +7 ) – ( 6x -4 -7 )
- 7x + 10 -8x + 4 = x -7 -6x + 11
-7x + 10 -8x +4 –x +7 + 6x -11
-10x +10
x = 10/-10
x = -1
11. – 18 – [ 3 ( x + 2 )
+ 4 ] = 21 – [ 6 ( 2x – 2 ) + 1 ]
- 18 – [
3x + 6 +4 ] = 21 [ 12x – 12 + 1 ]
- 18 – [
3x + 10 ] = 21 – [ 12x -11 ]
- 18 – 3x
-10 = 21 – 12x + 11
- 3x – 28
= - 12x + 32
- 18 – 32
= 3x – 12x
- 50 = -
9x
x = -50/-9
x = 5.5
No hay comentarios:
Publicar un comentario